Two‐Year Observations of the Jupiter Polar Regions by JIRAM on Board Juno. Issue 6 (15th June 2020) - Adriani, A.; Bracco, A.; Grassi, D.; Moriconi, M. L.; Mura, A.; Orton, G.; Altieri, F.; Ingersoll, A.; Atreya, S. K.; Lunine, J. I.; Migliorini, A.; Noschese, R.; et al.
Abstract: We observed the evolution of Jupiter's polar cyclonic structures over two years between February 2017 and February 2019, using polar observations by the Jovian InfraRed Auroral Mapper, JIRAM, on the Juno mission. Images and spectra were collected by the instrument in the 5‐μm wavelength range. The images were used to monitor the development of the cyclonic and anticyclonic structures at latitudes higher than 80° both in the northern and the southern hemispheres. Spectroscopic measurements were then used to monitor the abundances of the minor atmospheric constituents water vapor, ammonia, phosphine, and germane in the polar regions, where the atmospheric optical depth is less than 1. Finally, we performed a comparative analysis with oceanic cyclones on Earth in an attempt to explain the spectral characteristics of the cyclonic structures we observe in Jupiter's polar atmosphere. Plain Language Summary: The Jovian InfraRed Auroral Mapper (JIRAM) is an instrument on‐board the Juno NASA spacecraft. It consists of an infrared camera, for mapping both Jupiter's auroras and atmosphere, and a spectrometer. In February 2017, the complex cyclonic structures that characterize the Jupiter's polar atmospheres were discovered. Here, we report the evolution of those cyclonic structures during the 2 years following the discovery. We use for this purpose infrared maps built by the JIRAM camera images collected at wavelengths around 5 μm. The cyclones have thick clouds that obstruct most of the view of the deeper atmosphere. However, some areas, near the cyclones, are only covered by thin clouds allowing the spectrometer to see deeper in the atmosphere. In those areas, the instrument was able to detect spectral signatures that permitted estimation of abundances of water vapor, ammonia, phosphine, and germane. Those gases are minor but significant constituents of the atmosphere. Finally, the dynamics of the Jupiter's polar atmosphere are not well understood and are still under study. Here, to suggest possible mechanisms that governs the polar dynamics, we attempted a comparative analysis with some Earth oceanic cyclones that show similarities with the Jupiter ones. Key Points: The Jupiter's polar cyclonic structures did not change much in two years of observations from February 2017 to February 2019 Abundances of some atmospheric minor constituents measured in the hottest spots of the polar regions, higher values registered in the south Earth oceanic cyclones analogies suggest a well‐mixed upper boundary layer on Jupiter's Poles